2019
DOI: 10.1136/archdischild-2019-317544
|View full text |Cite
|
Sign up to set email alerts
|

Placing education at the centre of the outpatient clinic improves learning and experiences for everyone using the multilevel attainment of learning, teaching and support (MALTS) approach

Abstract: A large proportion of consultant time is spent in outpatient practice. This setting provides an excellent learning environment for different levels of a trainee if well organised. This article describes an evidence-based teaching approach and its evaluation by trainees, patients and carers in a typical district general hospital setting which it is hoped others might find helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Like some other studies, this study indicates that various patient management skills can be improved within the outpatient setting [ 10 , 23 , 26 , 30 33 ].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Like some other studies, this study indicates that various patient management skills can be improved within the outpatient setting [ 10 , 23 , 26 , 30 33 ].…”
Section: Discussionsupporting
confidence: 74%
“…The decision about which methods to use is extremely complex and influenced by factors such as student knowledge level, learning objectives, as mentioned by our participants, teacher experiences, educational funding, facilities, and equipment [ 34 , 35 ]. Using textbooks and researching educational materials before patient visits are also valued by trainees [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, this has led to the understanding that in order to use new knowledge in clinical practice, medical learners need to be encouraged and supported to process the knowledge, rather than listen to it being delivered by a more experienced physician [5]. In addition, it has been shown that pediatric and other residents flourish in a supportive learning environment, rather than work hard, see lots of patients, and learn on the fly [6,7]. Such insights from educational science may have a considerable impact on our daily educational practice in the workplace.…”
mentioning
confidence: 99%